Let f:R→R is a function defined by f(x)=3x-4, then f-1(x) is 

Let f:RR is a function defined by f(x)=3x-4, then f-1(x) is 

  1. A

    13x+4

  2. B

    13x-4

  3. C

    3x+4

  4. D

    not defined

    Register to Get Free Mock Test and Study Material

    +91

    Verify OTP Code (required)

    I agree to the terms and conditions and privacy policy.

    Solution:

    f:RR  f(x)=3 x -4
    f is one-one onto function.
    Let                   y=3x-4
                               x=y+43
    Replace x by yy=x+43=f-1(x) 
     

    Chat on WhatsApp Call Infinity Learn

      Register to Get Free Mock Test and Study Material

      +91

      Verify OTP Code (required)

      I agree to the terms and conditions and privacy policy.